فلسفة الدين عند سبينوزا - شباني, منذر; ناصر, خضر (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The impact of Spinoza's criticism of the religious phenomenon along with its relation to human beingshas been greatly evident on theintellectual climate of modern philosophy in general, and the Study of the philosophy of religion that emerged with Kant later in particular.Thus, we can assert that the philosophical trend of Spinoza has paved the wayfor Kant’s researches to go on in this direction.Consequently, his researches have been influenced by the achievements of the intellectual and cultural environment that prevailed at that time; from Bruno and Descartes to Copernicus and Galileo walked libertarian direction of mental ahead in the criticism of the principles underlying philosophical and natural thought in the sixteenth and seventeenth century، but none of those have had the intellectual courage to put religion into criticism. Especially, withina religious environment that has been dominated by exceptional religiosityin order to face the expected danger of philosophers and thinkers.Within this atmosphere of exceptional religiosity, Spinoza has logically criticized all sacred things of his time such as: the Holy Bible, the nature of God, the relationship between faith and reason, the concept of miracle, prophecy, and the afterlife. He has raised many doubts aboutthe whole religious phenomenon calling for conducting many researches and teststhat might lay bare the hidden truth that religion claimed to have and being the everlasting salvation for human kind.By doing so, he has created a novel philosophical trend that has been known today as the philosophy of religion. أثر نقد سبينوزا للظاهرة الدينية واتصالها بالإنسان؛ في المناخ الفكري للفلسفة الحديثة بشكل كبير، ولا سيما في مبحث فلسفة الدين الذي ظهر مع كانط فيما بعد، بحيث يمكن أن نعدّ فلسفة سبينوزا، الإرهاص الكبير الذي دفع بأبحاث كانط في هذا الاتجاه، متأثراً في ذلك بمنجزات البيئة الفكرية والثقافية التي كانت سائدة في عصره، فمن برونو وديكارت إلى كوبرنيكوس وغاليلي سار الاتجاه التحرري العقلي متقدماً في نقد المبادئ التي يقوم عليها الفكر الفلسفي والطبيعي في القرن السادس والسابع عشر، لكن أياً من هؤلاء لم يمتلك الجرأة الفكرية لوضع الدين موضع النقد، في بيئة دينية غلب عليها طابع التشدد لمواجهة الخطر القادم في رجال الفكر.في هذا الجو المشحون بالتعصب تناول سبينوزا بنقده أعظم مقدسات عصره: الكتاب المقدس، طبيعة الله، علاقة الإيمان بالعقل، مفهوم المعجزة، النبوة، الآخرة، بمنهج عقلي صرف، فوضع بذلك الظاهرة الدينية برمتها موضع إشكال يستوجب البحث والتدقيق عن مدى امتلاك الدين للحقيقة التي يدعيها، ومدى صلاحيته لتحقيق غاية الإنسان في الخلاص، واتجه بذلك اتجاهاً فلسفياً جديداً أثمر ما بات يُعرف باسم فلسفة الدين.